Fiqh Scripts of Bukit Gombak: Codicology and Contenst Analysis - Basri Na'ali; Fahmil Samiran (At-turas: Jurnal Studi Keislaman)
Abstract: Minangkabau has local cultural heritage, one of whichis ini the form of scripts such as those found in villagae Bukit Gombak on Padang Laweh. With the physical condition of the manuscript without a title, not intact, has neat scripts, is in Arabic but some of the pages are still radable. So that the formulation in this study is how describe and transliterate the Bukit Gombak fiqh text, what is the background of its emergence and whats is the contents of the Bukit Gombak fiqh manuscripts. The research method used is a philological approach with field research conducted in Jorong Bukit Gombak with data collection methods for document studies, inventory, codicology and interviews and the primary data source is Bukit Gombak fiqh manuscript while the secondary data sources are books, articles related to philology using qualitative analysis techniques with the stages of reduction, data study, further analysis, drawing conclusions. The results in this study are the Bukit Gombak fiqh text physically using Arabic writing in red and black ink with paper color brown, withour a titile and witho an author that found in one of the residents houses in village Bukit Gombak. The Bukit Gombak fiqh manuscripts containts fiqh ini general such as the book of marriage, the book of muamalah, the book of pilgrimage, the book of fasting. The history of writing the Bukit Gombak fiqh manuscript is estimated in the 18th century of fiqh manuscripts into Indonesia, which on average belonged to the shafi’i madhhab.